Fish behavior. - Quignard, Jean-Pierre (Ecological sciences series, 2020)
Advances in underwater exploration, in situ observation of fish populations, as well as the development of cutting-edge technologies, provide modern insights into behaviors and strategies of fish, whose cognitive abilities have long been underestimated and undervalued. Fish Behavior 1 presents current knowledge about fish biology, ecology and ethology. In light of the most recent scientific work, this book examines the habitats exploited by fish, as well as the strategies and tactics they have adopted regarding the occupation of available territories. It also addresses communication issues between individuals during social interactions. This book is intended for researchers, teachers, master#x92;s and doctoral students in biology and biogeography, engineers and technicians responsible for the development and protection of natural environments and public aquariums, in addition to aquaculturists, fishermen, environmentalists and ecologists.